QTL-seq analysis identifies two genomic regions determining the heading date of foxtail millet, Setaria italica (L.) P.Beauv - Yoshitsu, Yuki (Breeding science, 2017)
Heading date is an important event to ensure successful seed production. Although foxtail millet (Setaria italica (L.) P.Beauv.) is an important foodstuff in semiarid regions around the world, the genetic basis determining heading date is unclear. To identify genomic regions regulating days to heading (DTH), we conducted a QTL-seq analysis based on combining whole-genome re-sequencing and bulked-segregant analysis of an F2 population derived from crosses between the middle-heading cultivar Shinanotsubuhime and the early-heading cultivar Yuikogane. Under field conditions, transgressive segregation of DTH toward late heading was observed in the F2 population. We made three types of bulk samples: Y-bulk (early-heading), S-bulk (late-heading) and L-bulk (extremely late-heading). By genome-wide comparison of SNPs in the Y-bulk vs. the S-bulk and the Y-bulk vs. the L-bulk, we identified two QTLs associated with DTH. The first QTL, qDTH2, was detected on chromosome 2 from the Y-bulk and S-bulk comparison. The second QTL, qDTH7, was detected on chromosome 7 from the Y-bulk and L-bulk comparison. The Shinanotsubuhime allele for qDTH2 caused late heading in the F2 population, whereas the Yuikogane allele for qDTH7 led to extremely late heading. These results suggest that allelic differences in both qDTH2 and qDTH7 determine regional adaptability in S. italica